Anti-anemia drug FG4592 retards the AKI-to-CKD transition by improving vascular regeneration and antioxidative capability. Issue 14 (30th July 2021) - Wu, Mengqiu; Chen, Weiyi; Miao, Mengqiu; Jin, Qianqian; Zhang, Shengnan; Bai, Mi; Fan, Jiaojiao; Zhang, Yue; Zhang, Aihua; Jia, Zhanjun; Huang, Songming
Abstract: Acute kidney injury (AKI) is a known risk factor for the development of chronic kidney disease (CKD), with no satisfactory strategy to prevent the progression of AKI to CKD. Damage to the renal vascular system and subsequent hypoxia are common contributors to both AKI and CKD. Hypoxia-inducible factor (HIF) is reported to protect the kidney from acute ischemic damage and a novel HIF stabilizer, FG4592 (Roxadustat), has become available in the clinic as an anti-anemia drug. However, the role of FG4592 in the AKI-to-CKD transition remains elusive. In the present study, we investigated the role of FG4592 in the AKI-to-CKD transition induced by unilateral kidney ischemia–reperfusion (UIR). The results showed that FG4592, given to mice 3 days after UIR, markedly alleviated kidney fibrosis and enhanced renal vascular regeneration, possibly via activating the HIF-1α/vascular endothelial growth factor A (VEGFA)/VEGF receptor 1 (VEGFR1) signaling pathway and driving the expression of the endogenous antioxidant superoxide dismutase 2 (SOD2). In accordance with the improved renal vascular regeneration and redox balance, the metabolic disorders of the UIR mice kidneys were also attenuated by treatment with FG4592. However, the inflammatory response in the UIR kidneys was not affected significantly by FG4592. Importantly, in the kidneys of CKD patients, we also observed enhanced HIF-1α expression which was positively correlated with the renal levels of VEGFA and SOD2. Together, these findings demonstrated the therapeutic effect of the anti-anemia drug FG4592 in preventing the AKI-to-CKD transition related to ischemia and the redox imbalance.